Strengthening the Understanding of Constitutionalism of Regional Heads Through Optimizing the Role of Regional Representative Councils in the Implementation of Regional Government - Putri Handayani Nasution (Abdimas Indonesian Journal, 2026)
The implementation of regional governance within a democratic state based on the rule of law requires the exercise of power based on the principles of constitutionalism. These principles include limitations on authority compliance with the law, respect for citizens' constitutional rights, and transparent and accountable governance. As the holder of executive authority at the regional level, the regional head holds a strategic position in managing government affairs, development, and public services. This broad authority requires an institutional oversight and balance mechanism to ensure that the exercise of power does not deviate from the principles of the rule of law. Within this framework, the Regional People's Representative Council (DPRD) holds a strategic position through the implementation of legislative, budgetary, and oversight functions. This community service activity is aimed at increasing understanding of the principles of constitutionalism in the implementation of the authority of the regional head and strengthening understanding of the DPRD's role in overseeing the implementation of regional governance. The activity is implemented using an educational and participatory approach through legal counseling, interactive dialogue, review of statutory provisions, and evaluation of participants' level of understanding. The material provided covers the principles of the rule of law, the limits of the regional head's authority, the institutional relationship between the regional head and the DPRD, and strategies for strengthening the DPRD's oversight function. This activity demonstrates that improving understanding of constitutionalism is crucial for building a proportional institutional relationship between regional heads and the Regional People's Representative Council (DPRD). Strengthening the DPRD's function is not intended to hinder the implementation of executive policies, but rather to serve as a constitutional instrument to ensure that regional governance remains based on the law, democratic principles, accountability, and the needs of the community.